Targeting Triple-Negative Breast Cancer by the Phytopolyphenol Carnosol: ROS-Dependent Mechanisms - Halima Alsamri; Yusra Al Dhaheri; Rabah Iratni (MDPI AG, 2023)
Triple-negative breast cancer (TNBC), which lacks the expression of the three hormone receptors (i.e., estrogen receptor, progesterone receptor, and human epidermal growth factor receptor), is characterized by a high proliferative index, high invasiveness, poor prognosis, early relapse, and a tendency to be present in advanced stages. These characteristics rank TNBC among the most aggressive and lethal forms of breast cancer. The lack of the three receptors renders conventional hormonal therapy ineffective against TNBC. Moreover, there are no clinically approved therapies that specifically target TNBC, and the currently used chemotherapeutic agents, such as cisplatin, taxanes, and other platinum compounds, have a limited clinical effect and develop chemoresistance over time. Phytochemicals have shown efficacy against several types of cancer, including TNBC, by targeting several pathways involved in cancer development and progression. In this review, we focus on one phytochemical carnosol, a natural polyphenolic terpenoid with strong anti-TNBC effects and its ROS-dependent molecular mechanisms of action. We discuss how carnosol targets key pathways and proteins regulating the cell cycle, growth, epigenetic regulators, invasion, and metastasis of TNBC. This review identifies carnosol as a potential novel targeting protein degradation molecule.